Epistemic Reasonableness and Respect for Persons. Issue 161 (1st December 2019) - Li, Zhuoyao
Abstract : Recent discussions by Martha Nussbaum and Steven Wall shed new light on the concept of reasonableness in political liberalism and whether the inclusion of epistemic elements in the concept necessarily makes political liberalism lose its antiperfectionist appeal. This article argues that Nussbaum's radical solution to eliminate the epistemic component of reasonableness is neither helpful nor necessary. Instead, adopting a revised understanding of epistemic reasonableness in terms of a weak view of rationality that is procedural, external and second-order rather than a strong view that is substantial, internal and first-order can help political liberalism maintain an epistemic dimension in the idea of reasonableness without becoming perfectionist. In addition, political liberalism can defend a stronger account of respect for persons against liberal perfectionism on the basis of the revised understanding of epistemic reasonableness. Both arguments serve to demonstrate the strength of the political liberal project.